Landscapes of fear - Tuan, Yi-Fu 1930- (University of Minnesota, 2013)
Landscapes of Fear is renowned geographer Yi-Fu TuanÕs influential exploration of the spaces of fear and of how these landscapes shift during our lives and vary throughout history. In this groundbreaking workÑnow with a new preface by the authorÑYi-Fu Tuan reaches back into our prehistory to discover what is universal and what is particular in our inheritance of fear.